Reordering Spatial and Social Relations: A Case Study of Professional and Managerial Flexworkers. (25th March 2013) - Richardson, Julia; McKenna, Steve
<x xml:space="preserve">Abstract</x> Research on flexible work practices has focused primarily on social relationships, individual identity, work/work–life balance experience and performance. This paper aims to add another dimension by focusing on space and, specifically, the performance of space by professional flexworkers as they reorder their home and work lives through the process of becoming flexworkers. Drawing on Law's 'modes of ordering' and Latourian actor network theory, as well as on Beyes and Steyaert's recent contribution on 'performing space', the paper considers how flexworkers themselves reorganize space(s) as an ongoing accomplishment. The purpose and contribution is to offer an alternative to the view that the home and work are rigid containers fixed in social structure, to one that views them as self‐referential space(s), reordered by flexworkers as they seek to 'keep the social moving'. The paper is based on an empirical study of employees in a Canadian subsidiary of a large hi‐tech multinational corporation. It examines organizational policy documents and interviews with managerial and non‐managerial flexworkers to identify how social and spatial relations are reordered and performed.